Improving women's access to quality sweetpotato vines - International Potato Center (2012)
AII of our delivery system efforts depend on vines getting to the right people at the right time. In Year 3 of SASHA we focused on better understanding of how gender affects the production and access to sweetpotato vines for planting {"seed") in the Lake Zone of Tanzania where the Marando Bora project was operating.